Learning how to twist fast - Yeadon, F. (coachesinfo.com, 1999)
Progressions are presented for learning aerial twisting forward single and double somersaults with one and a half twists and backward single and double somersaults with one twist. These progressions are based on the results of computer simulations and make a single change in technique from one stage to the next. They are best introduced on trampoline and then transferred to the gymnastics apparatus. It is possible to make rapid progress in learning complex skills in relative safety provided that consistency is achieved at each stage before progressing to the next. The advantage of using aerial twist is that it makes takeoff and landing much easier and safer.